Optimasi Threshold Support Vector Machine Menggunakan Statistik Youden untuk Klasifikasi Daerah Tertinggal di Indonesia - Mohammad Wildan Nurul Haqqi; Abdul Kudus (Jurnal Riset Statistika, 2026)
Abstract. Regional disparities in development and economic conditions in Indonesia have led to the emergence of underdeveloped regions with socioeconomic characteristics that differ substantially from non-underdeveloped regions. This condition results in class imbalance, where the number of underdeveloped regions is relatively smaller, causing classification models to be biased toward the majority class. Support Vector Machine (SVM) is a classification method that performs well in high-dimensional data and is robust to feature correlation; however, its performance on imbalanced data is highly influenced by hyperparameter selection and threshold determination. This study aims to identify the best SVM model through hyperparameter optimization using Grid Search and to optimize the classification threshold using Youden’s Statistic on underdeveloped region status data defined in Presidential Regulation No. 63 of 2020. The results indicate that the best model is obtained using a linear kernel with C = 1 and an optimal threshold of −0.401. The application of this threshold increases the F1-score from 0.917 to 0.923 and reduces the number of false negatives to zero, indicating an improved ability of the model to detect the minority class, namely underdeveloped regions. These findings provide practical implications for supporting more targeted decision-making by the government in prioritizing development and interventions for underdeveloped areas. Abstrak. Ketimpangan pembangunan dan kondisi ekonomi antarwilayah di Indonesia menyebabkan adanya daerah tertinggal dengan karakteristik sosial ekonomi yang berbeda dibandingkan daerah tidak tertinggal. Kondisi tersebut menimbulkan permasalahan ketidakseimbangan kelas atau kategori, di mana jumlah daerah tertinggal relatif lebih sedikit sehingga model cenderung bias terhadap kelas mayoritas. Penelitian ini bertujuan untuk menentukan model SVM terbaik melalui optimasi hyperparameter menggunakan Grid Search serta mengoptimalkan threshold menggunakan Statistik Youden pada data status daerah tertinggal yang ditetapkan dalam Peraturan Presiden No. 63 Tahun 2020. Support Vector Machine (SVM) merupakan metode klasifikasi yang optimal pada data berdimensi tinggi dan robust terhadap korelasi antarfitur, namun kinerjanya pada data tidak seimbang sangat dipengaruhi oleh pemilihan hyperparameter dan penentuan threshold yang tepat. Hasil penelitian menunjukkan bahwa model SVM terbaik adalah kernel linear, C = 1, dan threshold optimal sebesar -0,401. Threshold optimal tersebut meningkatkan F1-Score dari 0,917 menjadi 0,923 serta menurunkan jumlah False Negative hingga nol, yang menunjukkan peningkatan kemampuan model dalam mendeteksi kelas minoritas atau daerah tertinggal. Temuan ini memberikan implikasi praktis dalam mendukung pengambilan keputusan yang lebih tepat sasaran bagi pemerintah dalam menentukan prioritas pembangunan dan intervensi pada daerah tertinggal.